Impacto da pandemia da COVID-19 na saúde mental e na educação da população LGBTQIA+ brasileira: um estudo da produção acadêmica-científica - Pimentel, Matheus Fernandes De Sousa (Universidade Federal de São Carlos, 2024)
The objective of this research was to identify, map, and analyze scientific publications on the impacts of the COVID-19 pandemic on the Brazilian LGBT population from 2020 to 2022. We aimed to analyze the knowledge production present in doctoral theses, master's dissertations, and scientific journal articles in the fields of psychology and education concerning the impact of the COVID-19 pandemic on the Brazilian LGBT population during this period. The research involved searching for scientific productions in electronic databases such as SciELO (Scientific Electronic Library Online), BVS – Psi (Virtual Health Library – Psychology Brazil), BDTD (Brazilian Digital Library of Theses and Dissertations), and the CAPES journal portal. We used Portuguese language descriptors such as “Mental health,” “LGBT,” “Homosexuality,” “Education,” “Transgender” or “Transsexuality,” “COVID-19,” “Sars-COV-2,” and their English equivalents. The search process resulted in a total of 22 manuscripts. The analysis of the studies consisted of different stages, including a preliminary reading of the bibliographic material, an exploratory reading to verify the adequacy of the information to the study's goals, a reflective or critical reading, and an interpretative reading to relate and integrate the content of the works with the research problem. Of the 22 journals found, only 8 specifically addressed the theme of this research, while the others were excluded after the mentioned analyses. We concluded that there is still not a great methodological variability in national and international studies on the topic, highlighting the need to encourage more research. Additionally, we identified a lack of interest in the subject during the study period, as well as the absence of specific government policies to address the issue, highlighting the vulnerability of the young LGBT+ population in health emergency contexts. Therefore, the current research project mentions Brazilian education and how gender and sexuality are addressed within the biology (high school) and science (elementary school) subjects, as well as the struggle and history of the LGBTQIA+ community. Finally, the different types of violence suffered by the LGBTQIA+ population are addressed, emphasizing domestic violence, which is very recurrent in the daily lives and homes of people who deviate from the cisheteronormative standard, mentioning mental health as the main impact of the pandemic.
Impact of the COVID-19 pandemic on the mental health and education of the brazilian LGBTQIA+ population: a study of academic-scientific production
Keywords: Saúde Mental; LGBT; Educação; COVID-19; Mental Health; Education; CIENCIAS HUMANAS::EDUCACAO